Gastric antral vascular ectasia, also known as watermelon stomach - diagnosis and treatment - Jurasz, Karolina; Podgórska, Dominika; Rzeska, Ewa; Sanecki, Miłosz; Tomczyk, Karolina; Chojnacka, Natalia; Klarycki, Jakub; Cymer, Radosław (Journal of Education, Health and Sport, 2024)
Gastric antral vascular ectasia (GAVE), also referred to as watermelon stomach is a rare disease accounting for about 4% of non-variceal upper gastrointestinal bleeding. It can manifest as occult bleeding requiring transfusion or acute gastrointestinal bleeding. This condition often coexists with liver cirrhosis, autoimmune diseases, heart failure, in patients post-bone marrow transplantation, or kidney failure. It is crucial to differentiate GAVE from portal hypertensive gastropathy (PHG), because despite a similar clinical presentation, the treatment for these conditions is different. Endoscopic diagnosis is necessary and in some cases, it may require further investigation and histopathological examination of the biopsy. Treatment is administered to patients with bleeding symptoms. Currently, the most commonly used treatment method is endoscopic thermal ablation using argon plasma coagulation. The focus of this work is to present essential information regarding the clinical picture, diagnosis and treatment of watermelon stomach.